2018
DOI: 10.1259/bjrcr.20180006
|View full text |Cite
|
Sign up to set email alerts
|

Gastrogastric intussusception in adults: a case report with review of the literature

Abstract: Intussusception of the gastrointestinal viscera is rarely encountered in adult patients and is frequently associated with a polypoidal lead point, which is often malignant. We would like to present the case of a 68-year-old male with a history of decompensated liver disease and multiple medical comorbidities, who was discovered to have an incidental gastrogastric intussusception on CT. No polypoidal lead point was seen and we believe this to be the first case of its kind to be described. We suggest that distor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 18 publications
3
28
1
Order By: Relevance
“…As similar to our case, there is the only one case report which described the absence of a polypoidal lead point in the patient who was diagnosed with the gastric intussusception. 3 One significant difference between the case which we have described and the previous case is that our patient does not have the complications associated with portal hypertension such…”
Section: Questionmentioning
confidence: 59%
“…As similar to our case, there is the only one case report which described the absence of a polypoidal lead point in the patient who was diagnosed with the gastric intussusception. 3 One significant difference between the case which we have described and the previous case is that our patient does not have the complications associated with portal hypertension such…”
Section: Questionmentioning
confidence: 59%
“…Very few reported cases have a benign etiology. 1 Non‐malignant ascites have been implicated as an etiology of gastrogastric intussusception in some reports during 2018–2020. 1 , 3 In 2019, an 82‐year‐old patient had a severe gastrogastric intussusception with a gastric volvulus and a hiatal hernia.…”
Section: Discussionmentioning
confidence: 99%
“…According to Behrooz et al, “the earliest known description of intussusception was made by the Dutch physician Paul Barbette in 1674, with the first successful manual reduction of an intussusception being performed by Sir Jonathan Hutchinson in 1871 in a 2‐year‐old girl.” 1 Adult patients comprise 5% of all intussusceptions with only 2 to 3 cases per million per year. Of those, only 10% of adult intussusceptions involve the stomach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, intussusception involving the proximal gastrointestinal tract such as the stomach is exceedingly rare. A recent literature review identified only 10 instances of gastro-gastric intussusception since 1950, all of which were associated with a mass, either benign or malignant, functioning as a lead point[4-13] (Table 1).…”
Section: Discussionmentioning
confidence: 99%